2015
DOI: 10.1007/s00125-015-3841-z
|View full text |Cite
|
Sign up to set email alerts
|

Meal sequence and glucose excursion, gastric emptying and incretin secretion in type 2 diabetes: a randomised, controlled crossover, exploratory trial

Abstract: Aims/hypothesisInvestigation of dietary therapy for diabetes has focused on meal size and composition; examination of the effects of meal sequence on postprandial glucose management is limited. The effects of fish or meat before rice on postprandial glucose excursion, gastric emptying and incretin secretions were investigated.MethodsThe experiment was a single centre, randomised controlled crossover, exploratory trial conducted in an outpatient ward of a private hospital in Osaka, Japan. Patients with type 2 d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
87
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 74 publications
(93 citation statements)
references
References 41 publications
(70 reference statements)
6
87
0
Order By: Relevance
“…Previous studies found that gastric emptying is modulated by meal composition. Food items rich in protein were shown to delay gastric emptying by a mechanism involving increased GLP-1 and glucagon secretion [26]. In line with this, we found both glucagon and GLP-1 increase after oral BCAA.…”
Section: Discussionsupporting
confidence: 78%
“…Previous studies found that gastric emptying is modulated by meal composition. Food items rich in protein were shown to delay gastric emptying by a mechanism involving increased GLP-1 and glucagon secretion [26]. In line with this, we found both glucagon and GLP-1 increase after oral BCAA.…”
Section: Discussionsupporting
confidence: 78%
“…Furthermore, foods rich in SF and MUF, but not in PUF, strongly enhance GIP secretion in humans17, 18. Thus, it is possible that DPP4i monotherapy, which increases the levels of biologically intact GIP, would exacerbate insulin resistance in type 2 diabetes patients who consume diets high in SF and MUF; and thereby lead to deterioration of the HLE DPP4i monotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…45,46 This effect is considered to result from the suppression of gluconeogenesis 47 and prolonged gastric emptying due to the incretin effect. 46 Whatever the mechanisms are, the "carbo-last" diet (i.e., eating carbohydrates last) appears to be useful.…”
Section: "Carbo-last" Diet (Ie Eating Carbohydrates Last)mentioning
confidence: 99%